Analisis SWOT Sebagai Pengembangan UMKM Berbasis Ekonomi Kreatif Destinasi Pariwisata Batik Kota Pekalongan - Wenti Ayu Sunarjo; Amalia Ilmiani; Arum Ardianingsih (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2019)
Creative economy that is very synonymous with creative industry activities, at the moment is considered capable of making a very significant contribution to the regional economy. Creative economy is essentially focused on industries that create goods and services that rely on expertise, talent and creativity as sustainable intellectual property. Micro, Small and Medium Enterprises (MSME’s) are one of the business sectors that can develop and be consistent in the national economy. MSME’s have always been a good place for the creation of productive employment.The purpose of this research was to formulate a SWOT analysis (Strengths, Weakness, Opportunities, Threats) on the development of creative economy as a step in developing creative economy-based Micro Small and Medium Enterprises (MSMEs) in Pekalongan City through applicable development strategies, while the objectives of the research These are MSMEs that are spread in Pekalongan City which have a carrying capacity for Pekalongan City batik tourism.The level of technological readiness in this research is at the basic research stage with its output target is to obtain data from observations and interviews with informants through questionnaires related to efforts made by creative economy-based MSMEs to drive batik tourism destinations in Pekalongan which become the leading sectors of Pekalongan City. Data analysis using descriptive analysis techniques with SWOT analysis (Strengths, Weakness, Opportunities, Threats) to create a strategy for the development of creative economy-based MSMEs as a driver of tourism destinations in Pekalongan City.